Development of food processing laboratory exercises as a method for gaining undergraduate research experience - Heermann, Melanie (Kansas State University, 2019)
Undergraduate research experiences are important in teaching research skills. Opportunities to participate in research projects with faculty members can be limited. Studies have found that course-embedded research opportunities serve as meaningful experiences for students if structured properly. Research was conducted to determine if selected exercises performed in an undergraduate food processing laboratory could serve as undergraduate research opportunities. Rolled sugar cookies were prepared according to AACC Method 10-50.05 using sucrose and alternative sweeteners, and evaluated for physicochemical and sensory attributes. Objectives were to evaluate the functional properties of alternative sweeteners in reduced-sugar cookies. Nine variations were prepared: control (C), Splenda for baking (S), Equal for baking (E), Truvia (T), Sweet’N Low (SNL), and 1:1 mixtures of sweeteners and sucrose. Cookies were characterized on width-to-thickness (W/T) ratio, moisture loss, color, hardness, fracturability, and sensory attributes. Significance level was determined by ANOVA and post-ANOVA Tukey’s multiple comparison tests. W/T ratios of T (7.2), T+sucrose (7.4), and C (7.8) were similar, but different from all other treatments. Color was similar for all treatments (ΔE: 80.190–84.075). T had greatest hardness (6878 N) and E had greatest fracturability (4622 N). The presence of sucrose decreased the fracture force (1359-1732 N). Control sensory attributes (appearance, texture, flavor, sweetness, and aftertaste) (6.07-6.89) significantly differed from alternative sweetener treatments (2.62-6.43). Physiochemical and sensory attributes of T+sucrose were closest to the control. This exercise introduced students to standard methods of sample preparation and physical and sensory analysis. Gluten-free sorghum breads, with varying inclusions of waxy sorghum flour, were prepared using an optimized gluten-free sorghum bread formulation (70% sorghum flour, 30% potato starch). Objectives were to determine the differences in physiochemical and sensory properties of sorghum bread with different waxy sorghum inclusions. Four treatments were prepared: control (0% waxy sorghum) (C), 15% waxy sorghum (15W), 25% waxy sorghum (25W), and 35% waxy sorghum (35W). Bread was characterized on loaf height, crust and crumb color, water activity, hardness, cohesiveness, springiness, and sensory attributes. Significance level was determined by ANOVA and post-ANOVA Tukey’s multiple comparison tests. Average loaf height was greatest for 35W (56.23 mm) and smallest for C (53.72 mm). C had the greatest average color change of the crust (ΔE=74.98) and crumb (ΔE=66.41). Average water activity remained constant (0.98-0.985). 15W had the greatest hardness (1060.98 N) and cohesiveness (0.91). C and 25W had the greatest springiness (0.69). 25W had the greatest sensory acceptability (6.0 out of 9). This exercise introduced students to research skills and challenges associated with gluten-free bread production. Student observations and perceptions about each of the previously mentioned exercises were assessed using surveys for each exercise. Questions were formatted on a Likert scale in four sections: demographics, physical and sensory properties, research and writing skills, and food processing knowledge. Sixty-five percent or more of students completing each survey gave positive responses. The large number of positive student responses indicate that students perceived each exercise as a beneficial learning experience. Students believed the exercises taught them important information about food processing, research principles, and scientific communication.
Keywords: Undergraduate research; Artificial sweeteners; Gluten free bread; Sorghum; Student-generated data